Ideas in politics in international context - Middleton, A (Wiley, 2023)
This article asks how we might rethink the study of ‘ideas in politics’ in modern Britain. It suggests that historians need to set the problem in its international contexts in a more structured way. Focussing on the nineteenth century, the article reflects on conceptual angles opened up by ‘global intellectual’ and ‘entangled’ approaches to political ideas and behaviour. While stressing that these methods have their pitfalls, the article argues that a reconsideration of the seams where international and intellectual contexts meet can help to reconnect modern British political history with wider historical debates.